2019
DOI: 10.1186/s13104-019-4171-x
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life among people living with HIV/AIDS in Togo: individuals and contextual effects

Abstract: ObjectiveThe objective of this study is to assess the quality of life and to identify factors associated with good global quality of life among people living with HIV/AIDS (PLWHA) in Togo.ResultsIn total, 880 PLWHA with mean age (standard deviation) of 39.6 (10.1) years, were interviewed. Most of them (78.4%) were female. The global score of quality of life was ranged from 42.6 to 112, with a mean (standard deviation) estimated at 86.3 ± (13.3). More than the three-quarters (76.2%) of the participants had a go… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
25
4
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 21 publications
4
25
4
5
Order By: Relevance
“…In this study, we observed that close to half of the participants (43%) had a good QoL. This finding compares with previous findings involving HIV patients on treatment from Ethiopia [ 23 , 24 ] and Togo [ 25 ]. The proportion of study participants with good QoL was even higher (>70%) according to other studies from sub-Saharan Africa [ 26 ].…”
Section: Discussionsupporting
confidence: 81%
“…In this study, we observed that close to half of the participants (43%) had a good QoL. This finding compares with previous findings involving HIV patients on treatment from Ethiopia [ 23 , 24 ] and Togo [ 25 ]. The proportion of study participants with good QoL was even higher (>70%) according to other studies from sub-Saharan Africa [ 26 ].…”
Section: Discussionsupporting
confidence: 81%
“…Better living conditions, greater awareness about HIV, and the anonymity people generally enjoy living in an urban setting likely creates a less-stigmatizing space for PLHIV. Our ndings that educational level, employment and income level was not associated with HRQoL however differs from reports in the literature which associates a better HRQoL among PLHIV with a higher level of education (18,20,(48)(49)(50); with employment (19,54,56) and relatedly to higher income levels (19,57). The prevailing socio-economic circumstances which is similar among participants irrespective of setting may likely be the explanation and can inform the additional interventions to explore for higher impact.…”
Section: Discussioncontrasting
confidence: 67%
“…Context such as place of residence has been shown to be associated with HRQoL in LMIC (20,21). Our study showed that urban participants at Ngokolo had higher HRQoL scores across most domains than did their rural counterparts at Bugisi.…”
Section: Discussionmentioning
confidence: 46%
“…The support from family largely depends on disclosure of sero-status, which is high in our study (86.25%). Disclosure is found to associated with QoL [44]. Family support can also help to improve adherence to HAART which in turn suppress viral load and improve clinical condition of patients, ultimately contribute for improved QoL.…”
Section: Plos Onementioning
confidence: 98%